Potensi Tepung Beras Kaya Pati Resisten Sebagai Bahan Pangan Inovatif - Rozali, Zalniati Fonna (Perum BULOG, 2018)
ABSTRACTChanges in lifestyle cause people to demand the availability of functional foods that are ready to eat, nutritious and positive for health as a part of the daily menu. A food ingredient can be said to be functional if it contains components (both nutritional and non-nutritional) which have beneficial physiological effects on the functions of organs in the body. The biological role of resistant starch as an ingredient of functional food is related to the ecology of